Dropping out of School? A Competing Risks Analysis of Young Immigrants? Progress in the Educational System - Vibeke Jakobsen; Michael Rosholm (Institute for the Study of Labor (IZA), 2003)
This paper analyses the drop-out and graduation behaviour of young 1st generation immigrants enrolled in a qualifying education in the period 1984-1999. The descriptive analyses show that the low educational achievements among young immigrants compared to young ethnic Danes found in other studies are a combination of low enrolment rates and high drop-out rates among the immigrants. Especially, male immigrants have much higher dropout rates and lower completion rates than ethnic Danes. A competing risk duration model is used to analyse the time patterns of drop-out rates and completion rates for immigrants, as well as the effects of variables such as age at migration, marital status, the presence of young children, parental education, and ethnic origin. The results show that marriage reduces the probability of educational enrolment for female immigrants as well as for male immigrants, but also that being (or becoming) married leads to a decline in the female immigrants? drop-out rate. Age at migration exerts a negative influence on the probability of enrolling in an education, and for women age at migration also affects the dropout rate. Parental capital shows no effect on the immigrants drop-out and completion rates.
Keywords: J24; J61; 330; educational achievement; drop-out; competing risks; duration model; sample selection; Abbrecher; Migranten; Jugendliche; Statistische Bestandsanalyse; Schätzung; Dänemark